Performance of geopolymer high strength concrete wall panels and cylinders when exposed to a hydrocarbon ﬁre - Mohd Ali, A.Z.; Sanjayan, Jay; Guerrieri, Maurice (Elsevier Science Ltd, 2017)
This study presents an investigation of the effect of hydrocarbon ﬁre exposure on the residual compres-sive strength properties of geopolymer concrete panels and cylinders. Gladstone ﬂyash was utilized as the binder whilst the alkaline solution/ﬂy-ash ratio and sodium silicate to sodium hydroxide (Na2SiO3/NaOH) ratio was 0.4 and 2.5 respectively. The compressive strength at the test date was 64 MPa. Two dif-ferent cylindrical specimens’ sizes (150 and 100 mm diameter